2018
DOI: 10.1108/ijqss-12-2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

Electronic medical record use and perceived medical error reduction

Abstract: Purpose -The purpose of this paper is to present the findings of a research study conducted to find the perceptions of medical professionals about reduction in medical errors using electronic medical records (EMRs). It presents the relationship between EMR use in medical facilities and the reduction in medical errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Administrative information is related to making clinical judgments and cost-sensitive decisions, for example formularies used in drug selection based on insurance benefits obtained by patients. c. Information from remote monitoring devices, which capture vital signs, heart or respiratory status, and real-time lab results.The benefits of interoperability are in accordance with study conducted byAkbarov et al (2015),Cresswell et al (2017),Mozaffar et al (2017),Jindal and Raziuddin (2018),Liao et al (2017),Pontefract el al. (2018), and Vaoditas et al (2018).Wu et al (2004) inLienhard and Legner (2014), states that computational tools can support clinicians in preventing medication errors Sedano et al (2011).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Administrative information is related to making clinical judgments and cost-sensitive decisions, for example formularies used in drug selection based on insurance benefits obtained by patients. c. Information from remote monitoring devices, which capture vital signs, heart or respiratory status, and real-time lab results.The benefits of interoperability are in accordance with study conducted byAkbarov et al (2015),Cresswell et al (2017),Mozaffar et al (2017),Jindal and Raziuddin (2018),Liao et al (2017),Pontefract el al. (2018), and Vaoditas et al (2018).Wu et al (2004) inLienhard and Legner (2014), states that computational tools can support clinicians in preventing medication errors Sedano et al (2011).…”
supporting
confidence: 89%
“…Interoperability or integrated information systems between primary and secondary service units (Akbarov et al, 2015); between health information systems (Topaz et al, 2018 andCresswell et al, 2017); and between (Vaoditas et al, 2019;Liao et al, 2017), can prevent medication errors because they can answer the three problems above. Interoperability also enables real time data updates (Mozaffar et al, 2017), data reconciliation with patients and patient families (Buning et al, 2017), preventing prescribing and recording errors (Pontefract et al, 2018;Suess et al, 2019), and evaluation diagnosis and service for patients remotely using communication technology (Jindal and Raziuddin, 2018), so that the incidence of medication errors can be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Health-care service providers operate in competitive and dynamic arenas and in an extremely challenging environment where service failures and errors are inevitable (Jindal and Raziuddin, 2018;Ndubisi, 2012aNdubisi, , 2012b. These service failures and errors pose serious threats to firmcustomer relationships, customer satisfaction and retention (Thornlow and Merwin, 2009) and can even lead to customers avoiding needed treatment or switching to other providers (Kessler and Mylod, 2011;Um and Lau, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of recent Human Factors and Ergonomics (HFE) literature from this area (health IT and EMR in healthcare), most studies focused on patient safety with investigating the better quality of care (Aiken et al, 2012; Brown et al, 2018; Marella et al, 2017; Middletone et al, 2013; Singh & Sittig, 2016). Meanwhile, many studies have suggested a strong association between health IT and EMR‐related errors with their types and causes (Jindal & Raziuddin, 2018; Qian et al, 2020; Yackel & Embi, 2010). By using the technology acceptance model (TAM), it also continued to study healthcare providers' acceptance and satisfaction with the healthcare IT environment and associated usability (Abraham et al, 2009; Hudson et al, 2018; Kazley & Ozcan, 2007; Makam et al, 2013; Sutton et al, 2019; Weeger & Gewald, 2015).…”
Section: Introductionmentioning
confidence: 99%